1997
DOI: 10.1097/00006123-199706000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Autoregulation in Normal Pressure Hydrocephalus

Abstract: We conclude that the underlying disease in the improved patients was ischemia, with a loss of autoregulatory capacity in the periventricular white matter caused by cerebrospinal fluid diffusion. Those who did not improve had irreversible brain damage in which the CBF reduction was secondary to metabolic depression and autoregulation was preserved. We also conclude that patients suspected of having normal pressure hydrocephalus will improve clinically after shunting if preoperative hemispheric CBF is greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 23 publications
1
52
1
2
Order By: Relevance
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by the inhalation method or single photon emission computed tomography (SPECT) utilizing radio-labeled materials including xenon-133, 70,[74][75][76]117) technetium-99m hexamethylpropyleneamine oxime ( 99m Tc-HMPAO), 54B) nonradioactive xenon-CT, 118) and positron emission tomography (PET) with [ 15-O]H 2 O. 82,90) In a study measuring CBF in 31 patients of suspected Chapter 1: Diagnosis iNPH with 99m Tc-HMPAO SPECT, 54B) reduced blood flow over a wide area, especially in the cortex and subcortical white matter of the frontal and temporal lobes (expansion of central low-flow area), is seen.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of CBF in NPH, including patients with iNPH, have been conducted by the inhalation method or single photon emission computed tomography (SPECT) utilizing radio-labeled materials including xenon-133, 70,[74][75][76]117) technetium-99m hexamethylpropyleneamine oxime ( 99m Tc-HMPAO), 54B) nonradioactive xenon-CT, 118) and positron emission tomography (PET) with [ 15-O]H 2 O. 82,90) In a study measuring CBF in 31 patients of suspected Chapter 1: Diagnosis iNPH with 99m Tc-HMPAO SPECT, 54B) reduced blood flow over a wide area, especially in the cortex and subcortical white matter of the frontal and temporal lobes (expansion of central low-flow area), is seen.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…54B) The involvement of autoregulatory impairment is still controversial. 70,74,82,118) Thus, CBF measurements can show diffuse or regional decrease of CBF in NPH, but they are insufficient for the definite diagnosis of iNPH and also insufficient for the indication of shunt surgery (Recommendation grade C). However, CBF studies are useful in differentiating iNPH from other disorders of dementia, including Alzheimer's disease.…”
Section: Cerebral Blood Flow (Cbf)mentioning
confidence: 99%
“…Loss of chemical autoregulation, the vessel response to blood CO 2 changes, may have been involved 20) and may be predictive of clinical outcome after VP shunt placement. 14,26) This mechanism was recently exam- fMR Imaging on Hydrocephalus ined in our chronic hydrocephalus model. 9) Activityinduced CBF increase can be considered as another type of autoregulation.…”
Section: Discussionmentioning
confidence: 84%
“…18,29 In neonates, semiquantitative studies using transcranial Doppler ultrasound have shown a decrease in the middle cerebral artery resistive index after shunt insertion, indicating a reduction in downstream resistance. 9,19 Near-infrared spectroscopy has demonstrated an increase in CBF in infantile hemorrhagic hydrocephalus after CSF removal.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…In neonatal hydrocephalus, a significant increase in CBF following a reduction in ICP is generally considered to indicate impaired autoregulation due to microvessel compression. 29 This would indicate that the reversible elevation in resistance is not caused by arteriolar spasm. Indeed, in a group of neonates with hydrocephalus, those with adequate cerebrovascular reserve did well with conservative treatment, whereas those with poor reserve required an operation.…”
mentioning
confidence: 99%